Perlindungan Hukum Pekerja Perjanjian Kerja Waktu Tertentu Pada PT. Wonokoyo Jaya Corp - Mohammad Hatta; Purwono Sungkowo Raharjo; Rosita Candrakirana (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2023)
Problems regarding the rights of workers/labourers who work in a company are still not fully fulfilled, especially for workers with a certain time work agreement system (PKWT). Therefore, the government issued implementing regulations for the Omnibus Law on the Job Creation Law, namely PP No. 35 of 2021 concerning PKWT, outsourcing, working time, work relations and rest time, and termination of employment (PHK) as an effort to realize the welfare of workers. However, in practice, there are still many companies that have not fully fulfilled their workers' rights. Based on this background, a study was compiled entitled "Legal Protection of Work Agreement Workers for a Certain Time at PT. Wonokoyo Jaya Corp.” the research method used by the author is empirical normative with data collection techniques using structured interviews with the personnel of PT Wonokoyo Jaya Corp. The results of the study show that the implementation of workers' rights has not been fully fulfilled, namely in the provision of compensation money given to PKWT workers after the contract is completed. Therefore, the government should tighten supervision over companies that have not implemented new policies for the sake of realizing worker welfare and workers must also understand the applicable policies so that companies cannot be deceived and companies provide socialisation to the community.